Heterogeneous visible light photocatalysis for selective organic transformations - Lang, Xianjun (2014)
The future development of chemistry entails environmentally friendly and energy sustainable alternatives for organic transformations. Visible light photocatalysis can address these challenges, as reflected by recent intensive scientific endeavours to this end. This review covers state-of-the-art accomplishments in visible-light-induced selective organic transformations by heterogeneous photocatalysis. The discussion comprises three sections based on the photocatalyst type: metal oxides such as TiO2, Nb2O5 and ZnO; plasmonic photocatalysts like nanostructured Au, Ag or Cu supported on metal oxides; and polymeric graphitic carbon nitride. Finally, recent strides in bridging the gap between photocatalysis and other areas of catalysis will be highlighted with the aim of overcoming the existing limitations of photocatalysis by developing more creative synthetic methodologies.